Induction of tunnelling nanotube-like structures by influenza A viruses requires the onset of apoptosis. - Daniel Weir; Calum Bentley-Abbot; Jack McCowan; Colin Loney; Edward Roberts; Edward Hutchinson (PLoS Pathogens)
As well as spreading through virions, influenza A viruses (IAVs) can evade antiviral drugs and neutralising antibodies by spreading directly from cell to cell. In cell culture this can occur by the induction of intercellular membrane connections known as tunnelling nanotube-like structures (TLSs), which are capable of trafficking the viral genome between cells. Here, we showed that TLSs are formed by IAV infected cells in vivo, and then used in vitro models to ask how IAVs induce their formation. We found that TLS formation is not induced by cytokine signalling from infected to uninfected cells, but induction does require intracellular IAV replication. IAV replication can form filamentous virions which have structural similarities to TLSs, but we found that TLS induction is independent of virion morphology. We therefore looked at the intracellular responses to infection and found that the induction of TLSs correlated with the induction of apoptosis. Furthermore, the ability of IAVs to drive TLS formation can be modulated by chemically inhibiting, or inducing apoptosis. Finally, we found that inhibiting apoptosis, which prevents IAVs from inducing TLSs, lead to a significant reduction in the ability of IAVs to directly spread between cells. Our results, which suggest that IAVs can control their ability to spread directly from cell to cell by driving infected cells into apoptosis, identifies a new way in which a virus can manipulate its host to evade antiviral immune responses.